Some Aspects of Feminist Translation in Practice (El Hilo de la Fabula, 2024)
A feminist translation approach based on the book in Spanish, Sexo, género y sexualidades. Introducción a la filosofía feminista, by Elsa Dorlin (Mexico: Universidad Veracruzana, 2024), is presented. Feminist translation strategies are described, demonstrating their utility in the co-creation of meaning when applied pertinently, and emphasizing the translator’s active agency. A descriptive and contrastive methodology of Translation Studies is applied.
Keywords: feminist translation, translation strategies, cultural dissemination, feminist philosophy, Elsa Dorlin.